Rehabilitation after coronary artery by-pass grafting and improved quality of life. Issue 2 (June 1990) - Hoad, N A; Crawford, I C
Abstract : Long waiting lists for coronary artery by-pass grafting often mean that patients have to endure a prolonged period of pre-operative disability, a known poor prognostic factor for their future quality of life and employment prospects. A survey of 60 patients who attended a post-operative rehabilitation course designed to restore their fitness and self-esteem, and hence their quality of life, has shown encouraging results. When questioned a mean 16 months later, 85 per cent are working and significant improvements have been seen in all four quality of life indicators assessed: job satisfaction, family life, social life and sex life. Significant improvements are also seen in their symptoms. Cardiac rehabilitation should be made more available following coronary artery by-pass grafting.